Yalta 1945: the Black Sea Straits and the War in the Far East - Mikhail Sergeyevich Monakov (Vestnik MGIMO-Universiteta, 2015)
In the scientific literature on the Yalta conference of leaders of the three powers of the coalition there are no studies that reveal its naval aspects. Meanwhile, among the issues that had significance for the Soviet delegation, they held even if not the first priority, but were quite prominent. In the Russian historiography attention to these matters appeared only in the early 1990s, most likely because the Soviet side in negotiations had a negative impact on the formation of the post-war world order. Contemporary Russian historians are in line with the tradition, a feature of which was a lack of attention to the maritime policy of the Soviet Union, especially in the 1921 - 1955. It is clear, however, that projects of this scale, which required the mobilization of all resources of the Soviet state, creation of the most advanced shipbuilding and entirely new industries for the country and high-tech industries, could not arise in a vacuum. Behind this processes were certain political goals, and when the war began Stalin stopped work on the first "big shipbuilding program" though it did not mean that he refused them. This hypothesis is based and presented in this article.